Hubungan Riwayat Kejang Demam Dengan Angka Kejadian Epilepsi Di Dr. Moewardi - Andretty, Pamela Rezy, dr. Listyo Asist Pujarini, M.Sc, Sp.S, dr. Dona Dewi Niriawati (2015)
Background : Febrile seizure was a seizure caused by increased of body temperature above 38.4°C without an infection of central nervous system on 6 months to 4 years old. Febrile seizure cause any disorder, such as epilepsy. Epilepsy refers to chronic brain disorder manifested by recurrent seizure and sometimes loss of conscious. In 2012, WHO evaluated almost 80% of epilepsy in the world occurred in poor countries. Epilepsy prevalence in developed countries was around 3.5-10.7 per 1000 population, epilepsy could be economical and social burdens. Treatment cost per epilepsy case in India was approximately US $ 344 in a year. Stigma in society also affects the patient's emotion which leads to social isolation. Aim : To know the association history of febrile seizure and epilepsy prevalence in Dr. Moewardi general hospital Methods : This study used analytic observational design with case control methods. The study was held in 9 to 20 January 2015 in Dr. Moewardi general hospital. Samples were all patients in neurologic clinic in Dr. Moewardi general hospital. Samples divided into 2 groups, each groups has 22 respondents. Samples were taken using purposive sampling. The association between history of febrile seizure and epilepsy prevalence as analyzed with Kolmogorov-Smirnov using SPSS program 17 for windows. Results : From 44 respondents, 12 male samples and 10 female samples of epilepsy with most age ranged 20-40 years old. Epilepsy patients who had history of febrile seizure were 14 and no history of febrile seizure were 8 samples. Result of Kolmogorov-Smirnov test was significant with p=0,002 (p<0,05) and OR=0.057 Conclusions : There is association history of febrile seizure and epilepsy prevalence in Dr. Moewardi general hospital (p<0.05) and OR=0.057.